PREVALENCE AND RISK FACTORS OF OSTEOPOROTIC FRACTURES IN ELDERLY PATIENTS: A HOSPITAL-BASED STUDY - Dr Ashok Kumar Bishnoi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Osteoporotic fractures represent a major global health burden, particularly affecting elderly populations with increasing prevalence in India. This study aimed to determine the prevalence and identify risk factors associated with osteoporotic fractures among elderly patients presenting to a tertiary care hospital.Methods: A cross-sectional observational study was conducted at American Institute of Medical Sciences, Udaipur, from June 2021 to December 2021. A total of 350 patients aged ≥60 years with osteoporotic fractures were enrolled through consecutive sampling. Data were collected using structured questionnaires covering demographic characteristics, clinical parameters, lifestyle factors, and laboratory investigations. Statistical analysis was performed using SPSS 25.0, employing chi-square tests and multivariate logistic regression analysis.Results: The study population comprised 62.3% females with mean age of 69.4±8.2 years. Hip fractures were most common (40.6%), followed by vertebral (25.4%) and wrist fractures (19.1%). Falls from standing height accounted for 82.0% of injury mechanisms. Vitamin D deficiency was present in 66.9% of participants, while inadequate calcium intake was observed in 76.3%. Multivariate analysis identified previous fracture history (OR:3.12), vitamin D deficiency (OR:2.78), inadequate calcium intake (OR:2.45), female gender (OR:2.34), and sedentary lifestyle (OR:1.89) as significant independent risk factors. Sedentary behavior was prevalent in 47.7% of participants, with limited sun exposure in 56.6%.Conclusion: The study revealed high prevalence of modifiable risk factors including vitamin D deficiency and inadequate calcium intake among elderly patients with osteoporotic fractures. Comprehensive prevention strategies addressing nutritional supplementation, lifestyle modifications, and targeted screening programs are essential for reducing fracture burden in this vulnerable population.